MANTIK ve MANTIK TARİHİ ÜZERİNE BİR DEĞERLENDİRME - Ali Durusoy (İslami İlimler Dergisi)
An overview on the history of logic is to be subject of this article. The circumstances and philosophical background that causes to emergence of Logic as a science are explained and afterward the developments in Logic are studied. After Socrates’ ‘concept’ and Plato’s ‘the metaphysics of concept’ Aristotle has built up the Logic, as an independent discipline from linguistics. The philosopher who has rebuilt up the logic in Arabic is Al-Farabi. Avicenna’s distinction of “tasavvur” (conception) and “tasdhik” (judgment) has provided to examine the logic with integrity in a way. However this integrity has not protected in modern eras. Hence the issues which deal with Logic, has been subject of methodology and philosophy of science, as became independent from logic. This also means the disintegrity of human mind. The central argument of this article is that we must overcome this disintegrity and integrate the logic with other sciences.